Tingginya Kadar Karboksihemoglobin (COHb), Hemoglobin (Hb), dan Hematokrit pada Montir Bengkel Motor di Kota Makassar - Pratiwi, Pratiwi; Anggria, Nirmawati; Rachman, Irwandi (HIGIENE: Jurnal Kesehatan Lingkungan, 2021)
Carbon monoxide (CO) is a gas that is poisonous. Carbon monoxide (CO) gas when it is in the blood can bind to hemoglobin because of the strong binding power of about 200 - 300 times compared to oxygen so that it forms a Carboxyhemoglobin (COHb) reaction which results in a decrease in the supply of oxygen for the body and accelerates the erythropoetic process which will increase the production of concentration hemoglobin and hematocrit. Mechanics are one of the most risky jobs due to exhaust emissions produced by motorized vehicles. The purpose of this study was to determine carboxyhemoglobin (COHb) levels, hemoglobin levels and hematocrit levels in the blood of a motorbike repair mechanic. This type of research was a descriptive study with cross-sectional design by analyzing carboxyhemoglobin (COHb) levels, hemoglobin levels and hematocrit levels of 30 motorbike repair mechanics work Manggala District, Makassar City. The spectrophotometric method was used to check the carboxyhemoglobin (COHb) level, while the hemoglobin test used the cyanmethemoglobin method and the hematocrit level examination used the hematocrit macrometode. From the results of laboratory tests, the carboxyhemoglobin (COHb) levels of all samples showed an increase (100.0%), while the hemoglobin and hematocrit levels showed 17 samples (56.7%) were normal and 13 samples (43.3%) increased. The results of the study, it was found that 13 samples had increased levels of carboxyhemoglobin (COHb), hemoglobin and hematocrit, indicating that the mechanic could indicate secondary polycythemia.